Use of Social Media as a Communication Media by Public Relations of Medan City Government - Sri Nurhayati; Nursapia Harahap (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
This study aims to determine how the use of social media as a medium of communication by public relations Medan city government). The results of the study show that: 1. Social media is very influential as a means of communication by the protocol and communication of the Medan City leadership, 2. Social media is very effectively used as a means of delivering information to the public, 3. There are no challenges faced as a protocol and communication for City leaders. Medan in using social media as a means of communication, 4. The existence of hoax news and differences of opinion are one of the inhibiting factors that occur as protocol and communication for Medan City leaders in conveying information, 5. The network is evenly distributed throughout the city of Medan, 6. The existence of hoax news and differences of opinion are also a challenge for the community in receiving information conveyed by the Public Relations of the Medan City Government through social media, 7. The community is also satisfied with the information obtained through social media.